Diffuse cutaneous leishmaniasis in an immunocompromised patient resembling histoid Hansen's disease - Asha Kumari; Manisha Balai; Lalit K Gupta; Ashok K Khare; Asit K Mittal; Sharad Mehta (Wolters Kluwer Medknow Publications, 2018)
Cutaneous leishmaniasis is caused by protozoan parasites of the genus Leishmania. Atypical presentation and widespread progression of the lesions may be seen in patients with HIV disease and diffuse cutaneous leishmaniasis and HIV co-infection is emerging as a serious new threat. We report a case of diffuse cutaneous leishmaniasis in a HIV- infected patient resembling Histoid Hansen.